2013
DOI: 10.1093/annonc/mdt351
|View full text |Cite
|
Sign up to set email alerts
|

Second-line chemotherapy versus supportive cancer treatment in advanced gastric cancer: a meta-analysis

Abstract: This meta-analysis demonstrated evidence to support second-line chemotherapy in advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
72
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 13 publications
1
72
0
1
Order By: Relevance
“…Compared with the best supportive care, first-line chemotherapy for advanced gastric cancer (AGC) improves survival time and quality of life (2)(3)(4); however, the median overall survival (OS) time is short (9-13 months) (5)(6)(7). Several previous studies have demonstrated that second-line chemotherapy confers a significant survival benefit over best supportive care in AGC, with median OS time ranging from 4 to 9.5 months (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the best supportive care, first-line chemotherapy for advanced gastric cancer (AGC) improves survival time and quality of life (2)(3)(4); however, the median overall survival (OS) time is short (9-13 months) (5)(6)(7). Several previous studies have demonstrated that second-line chemotherapy confers a significant survival benefit over best supportive care in AGC, with median OS time ranging from 4 to 9.5 months (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The results of two randomized controlled trials (RCTs) were published, revealing an OS benefit from treatments with irinotecan or docetaxel compared with best supportive care (BSC) alone in patients for whom one or two prior treatments had failed (13,14). Recently, Kim et al (15) reported a meta-analysis in which a significant reduction in the risk of death was observed in patients receiving salvage chemotherapy compared with supportive cancer treatment. This provided evidence for implementing second-line chemotherapy in patients with AGC.…”
Section: Introductionmentioning
confidence: 99%
“…Average median overall survival ranges from 4.3 months to 11 months, and is better with a combination of chemotherapy agents [5]. Even more, salvage chemotherapy leads to a significant reduction in the risk of death when compared to best supportive care [6,7]. Data analysis from palliative chemotherapy results show an overall survival of 8-12 months [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%